2020
DOI: 10.1111/ijcp.13854
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of ambient temperature and ultraviolet radiation on the incidence of herpes zoster: An ecological study in Taiwan

Abstract: The aim of the study was to examine the relationship between ambient temperature, ultraviolet radiation, and the development of herpes zoster in Taiwan. An ecological study was conducted to analyse the database of the Taiwan National Health Insurance Programme. Participants aged ≥20 years with newly diagnosed herpes zoster between 2003 and 2012 were selected for analysis. The monthly incidence rate of herpes zoster was measured between 2003 and 2012. Monthly average ambient temperature in Celsius (°C) between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In South Korea, a nationwide large-scale study utilized GAM and generalized linear model (GLM) to focus on the relationship between ambient temperature and HZ, which showed that a higher ambient temperature resulted in an increased risk of HZ incidence rate [17]. Another ecological study suggested the relationship between the monthly incidence rate of HZ, and the analysis of the monthly average temperature found that high temperature is a hazard factor for HZ [18]. However, the majority of the research has mainly focused on understanding how temperature affects the frequency of HZ, and there is little if any data on how other meteorological conditions, including humidity, affect the number of patients with HZ.…”
Section: Of 12mentioning
confidence: 99%
“…In South Korea, a nationwide large-scale study utilized GAM and generalized linear model (GLM) to focus on the relationship between ambient temperature and HZ, which showed that a higher ambient temperature resulted in an increased risk of HZ incidence rate [17]. Another ecological study suggested the relationship between the monthly incidence rate of HZ, and the analysis of the monthly average temperature found that high temperature is a hazard factor for HZ [18]. However, the majority of the research has mainly focused on understanding how temperature affects the frequency of HZ, and there is little if any data on how other meteorological conditions, including humidity, affect the number of patients with HZ.…”
Section: Of 12mentioning
confidence: 99%